2013
DOI: 10.1002/pbc.24530
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization in sickle cell anemia in the era of extended red cell typing

Abstract: Despite extended RBC typing, alloimmunization may still occur due to RBC variants that are not detected on routine screening and transfusions at institutions where extended RBC typing is not done. Extended RBC typing should be the standard of care for patients with SCD. Prospective genotyping may reduce allosensitization to rare variants not detected on routine screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 21 publications
0
61
0
Order By: Relevance
“…Significant differences in RBC antigen frequencies between Caucasian donors and African and Afro-Caribbean recipients contribute to increased rates of alloimmunisation (Vichinsky et al, 1990). The use of Rh-and K-matched units has reduced alloimmunisation and haemolytic transfusion reactions, but sensitisation continues against Rh variants that are identifiable on molecular genotyping but not by serological methods (Lasalle-Williams et al, 2011;Noizat-Pirenne & Tournamille, 2011;Chou et al, 2013;Miller et al, 2013;O'Suoji et al, 2013).…”
Section: Alloimmunisation In Scdmentioning
confidence: 99%
“…Significant differences in RBC antigen frequencies between Caucasian donors and African and Afro-Caribbean recipients contribute to increased rates of alloimmunisation (Vichinsky et al, 1990). The use of Rh-and K-matched units has reduced alloimmunisation and haemolytic transfusion reactions, but sensitisation continues against Rh variants that are identifiable on molecular genotyping but not by serological methods (Lasalle-Williams et al, 2011;Noizat-Pirenne & Tournamille, 2011;Chou et al, 2013;Miller et al, 2013;O'Suoji et al, 2013).…”
Section: Alloimmunisation In Scdmentioning
confidence: 99%
“…Although single-institution and prospective multi-institutional studies have shown that limited C-, E-, and K-phenotype-matched RBCs significantly reduce the incidence of alloantibody production in SCD, 37,38,52 there remains no universal standard of care. More than 90% of institutions with Comprehensive Sickle Cell Centers provide RBCs that are prophylactically matched for C, E, and K to patients with SCD, 53 but only one-third of transfusion services nationally have such a policy.…”
Section: Strategies To Prevent Alloimmunization Rbc Antigen-matching mentioning
confidence: 99%
“…In a recent single-institution study of pediatric patients with SCD for whom limited RBC antigen-matching for C, E, K is practiced, 16 of 180 transfused patients formed 9 anti-C, 7 anti-E, and 5 anti-K antibodies. 38 The majority of cases were ascribed to transfusion at outside institutions that may not provide C-, E-, and K-matched RBCs, but 5 antibodies against Rh antigens occurred in patients who had Rh variants revealed by RH genotyping. We also recently reported a high rate of Rh alloimmunization in 182 transfused patients with SCD despite C-, E-, and K-matched RBCs primarily from African-American donors.…”
Section: Prevalence Of Alloimmunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact number of cumulative transfusions from birth to first antibody formation is often not reported and in many studies it is unclear if the transfusion history has been fully traced, including transfusions outside the reporting centers [9,10,12,[14][15][16]28]. Yet, the exposure to foreign RBC antigens is a prerequisite for alloimmunization and higher incidences of alloimmunization have been observed in patients with a higher number of transfusions [5,7,8,27,29].…”
mentioning
confidence: 99%